The role of innate immunity in spontaneous preterm labor: A systematic review - Areia, Ana Luísa (2019)
Background: Immunoinflammatory response by innate immunity components is a field with increasing interest in understanding the mechanisms behind preterm labor (PTL). Objectives: Systematic review of the role of innate immunity in spontaneous PTL. Study design: PubMed, Scopus, ClinicalTrials.gov and Web of Science were searched using pregnancy AND innate OR toll-like OR natural-killer OR dendritic AND delivery OR premature OR rupture of membranes. Main outcome measures: All article titles and abstracts were evaluated by two individuals, based in strict predefined inclusion criteria. For relevant studies, title, abstract, and full text were assessed to identify PTL and innate immunity studies, excluding multiple pregnancies, cervical insufficiency and indicated PTL. Results: From 894 articles evaluated, 101 full texts articles were assessed independently. For this systematic review 44 studies were finally included. Toll-like receptors 2 and 4 mediated immune dysfunction and inflammation can result in PTL. Moreover, PTL is linked to high levels of CD14+ monocytes; neutrophils seem important in inflammation-associated PTL and in pathological preterm premature rupture of membranes. Besides, decidual natural-killer cells and premature activation of dendritic cells may also participate in the etiology of PTL. Finally, dysregulation of maternal complement might increase the risk of PTL, characterized by high levels of innate lymphoid cells 2 and 3. Conclusions: Further research is warranted to ascertain the precise role of innate immunity in PTL. Nonetheless, our results indicate that Toll-like receptors, monocytes, natural-killer cells, dendritic cells and complement have significant roles in PTL.